A UHF/UWB Hybrid RFID Tag With a 51-m Energy-Harvesting Sensitivity for Remote Vital-Sign Monitoring - Lyu, Hongming; Wang, Zeyu; Babakhani, Aydin (IEEE transactions on microwave theory and techniques, 2020)
A novel ultrahigh frequency (UHF)/ultrawideband (UWB) hybrid radio frequency identification (RFID) tag is reported for object-specific remote vital-sign monitoring application. The tag achieves a record energy-harvesting sensitivity at the UHF band by codesigning a meander dipole antenna and a passive rectifier. The especially high quality-factor makes the frontend sensitive to near-field motions such as heartbeats and respiration in a wearable setting. The custom CMOS integrated circuit (IC) of approximately 1- μ \text{W} power consumption builds around a low-power UWB transmitter and converts the variations in the supply voltage to the impulse repetition rate. The tag consisting of the IC and UHF/UWB antennas requires no other discrete components and features a size of 4.2 cm ×2.9 cm and a weight of 0.93 g. A long-distance experiment verifies that the tag can be wirelessly powered up at 51 m from a 4-W effective-isotropic-radiation-power UHF transmitter. Remote vital-sign monitoring is validated on a human subject, in which the UHF power source is placed 2 m away from the subject with a power emission of less than 20 dBm. This work proposes a first-of-its-kind remote vital-sign monitoring solution based on a passively powered noncontact wearable tag. The design of the far-field energy-harvesting frontend with a record sensitivity serves as a reference for future works on battery-free remote sensors.